Effect of synthesis methods on the physico-chemical and catalytic properties of Ni 13X and Ni 5A zeolite catalysts in CO2 methanation - Wei, Liangyuan; Kumar, Narendra; Haije, Wim; Peltonen, Janne; Peurla, Markus; Grenman, Henrik; de Jong, Wiebren (ELSEVIER, 2025)
Zeolite 13X and 5A were modified with nickel using three different methods: evaporation impregnation, deposition precipitation, and ion-exchange for comparison in CO2 methanation. The catalysts were tested in a lab scale fixed bed reactor and their physico-chemical properties were characterized by XRD, SEM-EDX, TEM, STEMEDX, nitrogen physisorption, H2-TPR and NH3-TPD. The physico-chemical characterization results of Ni modified 13X and 5A zeolite catalysts showed that the zeolite structure did not change after the Ni modification by different catalyst synthesis methods, although the surface area and micro-pore volume decreased. The average diameter of NiO and the NiO cluster size range of Ni zeolite catalyst synthesized with ion exchange are smaller than the catalysts prepared by the evaporation impregnation and deposition preparation. Ni dispersed well through 13X, while a lot of Ni appeared on the crystal outer surface of 5A zeolite. Evaporation impregnation and deposition precipitation prepared Ni13X catalysts exhibited a higher activity than ion-exchange prepared samples on CO2 methanation. The catalyst performance of Ni5A-IE and Ni13X-IE zeolite catalysts, which were synthesized using the ion-exchange method for CO2 methanation was limited by the actual loading of Ni. The Ni 13X catalysts have less CH4 selectivity which could be attributed to their lower acidity. Ni13X-EIM catalyst showed good catalytic stability at 360 °C, with no catalyst deactivation during a 200 h catalyst stability test.